DIRECTIVES SPEECH ACTS ANALYSIS IN TEACHING VOCABULARY OF THE EIGHT GRADE STUDENTS OF MTS HUSNUL KHATIMAH IN THE ACADEMIC YEAR 2011-2012 - Rayda Ary Ana; Siti Musarokah (Universitas PGRI Semarang, 2012)
The utterances produced by people have speech acts, especially in the English teaching learning process. One of them is directive speech acts. Thus, this study aimed at identifying the directive speech acts and its functions in teaching vocabulary of the eight grade students of MTs Husnul Khatimah in the academic year 2011-2012. This study was carried out under a descriptive qualitative method. The data of this study were taken from the eighth grade students. The sample of the study was 30 students. The writers conducted the study in one meeting when the class was studying vocabularies in a recount text. The data were collected by recording the utterances produced by the teacher and the students. Then, the writer transcribed the record of the data. It was analyzed by identifying directive speech acts of the utterances and describing the functions of the directive speech acts. The writers found that there are twenty directives speech acts during the teaching learning process. All of them are imperatives or commands. The teacher uttered twenty-three orders to the students, while the students uttered one request to the teacher. The teacher directive speech acts have functions as a command, permission, prohibition and encouragement to the students.